PENGARUH DISIPLIN KERJA, BEBAN KERJA, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION PADA PT. DELKA KARYA MARITIM - Safira Hayati; Shofyan Roni (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study aims to analyze the effect of work discipline, workload, and work environment on turnover intention among employees at PT. Delka Karya Maritim. The method used in this research is multiple linear regression analysis with partial (t-test) and simultaneous (F-test) testing. The partial test results show that the work discipline variable does not have a significant effect on turnover intention, with a t-count value of -1.876 < t-table 1.98896 and a significance value of 0.064 > 0.05. On the other hand, workload has a positive and significant effect on turnover intention, with a t-count of 9.785 > 1.98896 and a significance value of 0.000 < 0.05. Meanwhile, the work environment does not significantly affect turnover intention, as indicated by a t-count of 0.407 < 1.98896 and a significance value of 0.685 > 0.05. However, the simultaneous test results show that work discipline, workload, and work environment together have a positive and significant effect on turnover intention. These findings indicate that although not all variables have a partial influence, collectively they contribute to employees’ intention to leave the company.